The Effect of Prebiotics, Alone or as Part of Synbiotics, on Cardiometabolic Parameters in Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Elham Razmpoosh; Mala S. Sivanandy; Alan M. Ehrlich (Biomedicines)
Background/Objectives: This systematic review and meta-analysis aimed to investigate the effect of prebiotics, alone or as part of synbiotics, on cardiometabolic parameters in polycystic ovary syndrome (PCOS) women. Methods: Databases, including PubMed, Scopus, ISI Web of Science, Embase, and the Cochrane Central Register of Controlled Trials, were searched for relevant randomized-controlled trials (RCTs) until 12 December 2024. Changes in mean ± standard deviations were extracted and combined using a random-effects model. Bias was assessed using Cochrane risk of bias and evidence quality with GRADE. Results: Twenty RCTs with 1271 participants were included. Results showed high-quality evidence supporting prebiotics’ effects, alone or as part of synbiotics, in reducing body-mass index [n = 853; weighted-mean difference (WMD): −0.510, 95%CI: −0.669, −0.351 kg/m2] and diastolic blood pressure (WMD: −2.218, 95%CI: −4.425, −0.010 mmHg), moderate-quality evidence for weight, waist-to-hip ratio, and triglycerides improvements, and low or very-low-quality evidence for waist circumference (WC), fat mass, fasting plasma glucose, fasting insulin, low-density lipoprotein (LDL), total cholesterol (TC), high sensitive-C reactive protein, total testosterone, follicle-stimulating hormone and free androgen index improvements. Subgroup analyses revealed possible reduction in LDL with prebiotics, as well as possible decreases in WC, TC, and total testosterone with synbiotics. Dietary approaches to stop hypertension diet improved insulin sensitivity. Conclusions: This study suggests that prebiotics may beneficially affect several cardiometabolic parameters in PCOS women. Approximately one-third of the results were based on moderate-to-high-quality evidence. This study highlights the need for future well-designed, larger RCTs with longer treatment duration to strengthen the evidence base and guide clinical decision-making.